ROAD IMPROVEMENT DESIGN ANALYSIS ON PANGLESERAN – CIBATU ROAD SECTION - Hanafiyah, Ali Akbar; Saputri, Utamy Sukmayu (ASTONJADRO, 2021)
Highways are an important means for people to reach their destination. The main function of the road is as a service provider of traffic movement, making it easier for people to reach their destination, distributing goods quickly safely, comfortably, and economically. The road is not always in good condition, even a lot of damage to the pavement before the age of the road plan is reached. There are many cases of early damage to roads in Sukabumi Regency that are found during road improvement / construction activities. Road Section: Pangleseran – Cibatu is one of them that will be carried out Road Improvement / Construction in 2022. Because this road section already exists, it will only be implemented overlay / additional layer only. In search of additional pavement thickness used component analysis method SKBI 2.3.26.1987. Based on the results of the analysis for the road section: Pangleseran - Cbatu obtained thick pavement additional layers for the age of the plan 5 years with a thickness of 10 cm, while for the age of the plan 10 years is with a thickness of 14 cm. Type of pavement for road section: Pangleseran - Cibatu is cement concrete. As for the causative factors of road damage is due to the level of heavy vehicles â‰¥ 8 tons increased, and drainage systems are clogged due to sediment and closed disposal by the surrounding community.